Development of Learning Module in The Culinary and Tourism Industry courses in Unimed Catering Study Program - Fridiarty, Lelly; Putri, Yuzia Eka; Anugerah, Ajeng Inggit (Journal of Community Research and Service, 2021)
This research is motivated by the absence of a learning module in the Culinary and Tourism Industry courses in the culinary study program, Medan State University. The purpose of this study was to see the process of developing modules for the Culinary and Tourism Industry subject matter, to determine the validity of the Culinary and Tourism Industry modules, to determine the practicality of the Culinary and Tourism Industry modules. The research method used in this research is the development method. The stages carried out in the development method are define, design, develop, and disseminate. The research instrument was in the form of a questionnaire that was distributed to research respondents, namely students and lecturers. The results of the study the validity of the learning module were declared valid from three aspects, namely format, content and language. The practicality of the culinary and tourism industry modules can be seen from the implementation of the use of learning modules. The result of module effectiveness assessment is very practical with a percentage of 84.06% of student responses and 77.083% with practical categories of lecturer responses. The effectiveness of the module is seen from the acquisition of students' pretest and posttest scores. Then analyzed the value of the increase through analysis of the gain score data. The gain score is 0.64 in the medium category.This research is limited to defining, designing and developing modules to obtain valid, practical and effective modules for student use. This research produces a product in the form of a learning module that can support the achievement of learning objectives in culinary and tourism courses